Antimicrobial Peptide Structure and Mechanism of Action: A Focus on the Role of Membrane Structure - Lee, Tzong-Hsien; N. Hall, Kristopher; Aguilar, Marie-Isabel (Current Topics in Medicinal Chemistry, 2016)
Antimicrobial peptides (AMPs) are showing increasing promise as potential candidate antibacterial drugs in the face of the rapidly emerging bacterial resistance to conventional antibiotics in recent years. The target of these peptides is the microbial membrane and there are numerous models to explain their mechanism of action ranging from pore formation to general membrane disruption. The interaction between the AMP and the target membrane is critical to the specificity and activity of these peptides. However, a precise understanding of the relationship between antimicrobial peptide structure and their cytolytic function in a range of organisms is still lacking. This is a result of the complex nature of the interactions of AMPs with the cell membrane, the mechanism of which can vary considerably between different classes of antimicrobia peptides. A wide range of biophysical techniques have been used to study the influence of a number of peptide and membrane properties on the cytolytic activity of these peptides in model membrane systems. Central to characterisation of this interaction is a quantitative analysis of the binding of peptide to the membrane and the coherent dynamic changes in membrane structure. Recently, dual polarization interferometry has been used to perform an in depth analysis of antimicrobial peptide induced membrane perturbation and with new mass-structure co-fitting kinetic analysis have allowed a real-time label free analysis of binding affinity and kinetics. We review these studies which describe multi-step mechanisms which are adopted by various AMPs in nature and may advance our approach to the development of a new generation of effective antimicrobial therapeutics.
Keywords: supported lipid bilayer